품질경영시스템이 흡수역량을 매개로 중소벤처 제조기업의 기업성과에 미치는 영향에 관한 실증연구 - 진성한; 이철규; 유왕진; Jin, Sunghan; Lee, Cheolgyu; Yoo, Wangjin (品質經營學會誌, 2013)
Purpose: This study is to search for the core factors of improving business performance of small and medium venture manufacturing company and to do an in-depth analysis of the relations with management performance through systematic approach and to provide implications of importance of the management for the improvement factors for the domestic small and medium venture manufacturing company. Methods: The data have been analyzed via the regression and path analysis using AMOS. Results: this study is absorptive capacity affects the business performance of manufacturing companies. absorptive capacity has the role of the parameters of the Quality Management System and business performance. Conclusion: This study suggests how to run absorptive capacity according to type of management performance, and how to enhance Quality Management System to efficiently promote absorptive capacity in order to grow of management performance. also, this study shows a way to enlarge the valuation standard for management and customer performance reflecting the growth potential of an enterprise in circumstance where the valuation standard focuses on financial performance.